2021
DOI: 10.3390/pharmaceutics13101605
|View full text |Cite
|
Sign up to set email alerts
|

PEGylated Mesoporous Silica Nanoparticles (MCM-41): A Promising Carrier for the Targeted Delivery of Fenbendazole into Prostrate Cancer Cells

Abstract: Low water solubility and thus low bioavailability limit the clinical application of fenbendazole (FBZ) as a potential anticancer drug. Solubilizing agents, such as Mobil Composition of Matter Number 41 (MCM) as a drug carrier, can improve the water solubility of drugs. In this study, PEGylated MCM (PEG-MCM) nanoparticles (NPs) were synthesized and loaded with FBZ (PEG-MCM-FBZ) to improve its solubility and, as a result, its cytotoxicity effect against human prostate cancer PC-3 cells. The loading efficiency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Molecule of the tetracaine was found inside the β-barrel for variants L58F, M107L (occ = 1.0 and occ = 1.0; PDB ID: 7BF7 and 7BF9, respectively), and on the protein surface near Arg124 and Trp19 for variant I56F (occ = 1.0; PDB ID: 7BF8). Based on the examples provided above and our own research findings, it can be concluded that presented variants of BLG has the potential to function as a carrier of PRM in term of thermodynamic and structural aspect.Therefore, the manipulation and engineering of BLG are important subjects for the further development of delivery systems, especially for poorly water-soluble compounds 72. In this regard, our findings referring to BLG variants of enhanced affinity to PRM, a topical anesthetic agent of low solubility (ca.…”
mentioning
confidence: 83%
“…Molecule of the tetracaine was found inside the β-barrel for variants L58F, M107L (occ = 1.0 and occ = 1.0; PDB ID: 7BF7 and 7BF9, respectively), and on the protein surface near Arg124 and Trp19 for variant I56F (occ = 1.0; PDB ID: 7BF8). Based on the examples provided above and our own research findings, it can be concluded that presented variants of BLG has the potential to function as a carrier of PRM in term of thermodynamic and structural aspect.Therefore, the manipulation and engineering of BLG are important subjects for the further development of delivery systems, especially for poorly water-soluble compounds 72. In this regard, our findings referring to BLG variants of enhanced affinity to PRM, a topical anesthetic agent of low solubility (ca.…”
mentioning
confidence: 83%
“…The water solubility of FBZ can be increased when serialized on β-lactoglobulin-modified MSNs, which can increase the cytotoxicity of FBZ and inhibit the migration of PCa cells ( Koohi et al, 2022 ). ( Figures 1A,B ) It is also possible to serialize FBZ on pegylated MSN (MCM-41) to improve its cytotoxicity and increase its delivery to PCa cells ( Esfahani et al, 2021 ).…”
Section: Mesoporous Silica Nanoparticles (Msns)mentioning
confidence: 99%
“…Different strategies have been examined to modify the physicochemical profile of fenbendazole, including solid dispersions, 16,17 cyclodextrins, 18 polymeric micelles, 19 nanocrystals, 20,21 and inorganic nanocarriers. 22 However, due to the high cost of production and issues with commercial scaling, the majority of these approaches may impose a large financial burden on developing countries. Another approach to addressing this issue is the development of multicomponent crystals (cocrystals and salts), which have shown great promise in improving and optimizing essential pharmaceutical properties such as solubility, dissolution rate, stability, and bioavailability of active pharmaceutical ingredients without changing their pharmacophore structure.…”
Section: Introductionmentioning
confidence: 99%